140k views
4 votes
Obtain the general solution to the equation. (x^2+10) + xy = 4x=0 The general solution is y(x) = ignoring lost solutions, if any.

1 Answer

3 votes

Answer:


y(x)=4+(C)/(√(x^2+10))

Explanation:

We are given that a differential equation


(x^2+10)y'+xy-4x=0

We have to find the general solution of given differential equation


y'+(x)/(x^2+10)y-(4x)/(x^2+10)=0


y'+(x)/(x^2+10)y=4(x)/(x^2+10)

Compare with


y'+P(x) y=Q(x)

We get


P(x)=(x)/(x^2+10)


Q(x)=(4x)/(x^2+10)

I.F=
e^{\int(x)/(x^2+10) dx}=e^{(1)/(2)ln(x^2+10)}


e^(ln\sqrt(x^2+10))=√(x^2+10)


y\cdot √(x^2+10)=\int (4x)/(x^2+10)* √(x^2+10) dx+C


y\cdot √(x^2+10)=\int (4x)/(√(x^2+10))+C


y\cdot √(x^2+10)=4√(x^2+10)+C


y(x)=4+(C)/(√(x^2+10))

User Bobflux
by
5.5k points